Hippocampal Glycerol-3-Phosphate Acyltransferases 4 and BDNF in the Progress of Obesity-Induced Depression - Huang, Yin-qiong; Wang, Yaofeng; Hu, Keyue; Lin, Shu; Lin, Xia-hong (Frontiers in Endocrinology, 2021)
Background Obesity has been reported to lead to increased incidence of depression. Glycerol-3-phosphate acyltransferases 4 (GPAT4) is involved in triacylglycerol synthesis and plays an important role in the occurrence of obesity. GPAT4 is the only one of GPAT family expressed in the brain. The aim of this study is to investigate if central GPAT4 is associated with obesity-related depression and its underlying mechanism. Results A high-fat diet resulted in increased body weight and blood lipid. HFD induced depression like behavior in the force swimming test, tail suspension test and sucrose preference test. HFD significantly up-regulated the expression of GPAT4 in hippocampus, IL-1β, IL-6, TNF-α and NF-κB, accompanied with down-regulation of BDNF expression in hippocampus and ventromedical hypothalamus, which was attributed to AMP-activated protein kinase (AMPK) and cAMP-response element binding protein (CREB). Conclusion Our findings suggest that hippocampal GPAT4 may participate in HFD induced depression through AMPK/CREB/BDNF pathway, which provides insights into a clinical target for obesity-associated depression intervention.